Archaeological implications of the digestion of starches by soil bacteria: Interaction among starches leads to differential preservation. (October 2017) - Hutschenreuther, Antje; Watzke, Jörg; Schmidt, Simone; Büdel, Thomas; Henry, Amanda G.
Abstract: Soil bacteria damage and destroy starch granules in archaeological contexts, but most studies of this kind of damage report on pairings of a single bacterial species with starches from a single plant species. Here we report the results of experiments in which starch granules from multiple plants were digested by a community of soil bacteria. The damage patterns of this bacterial community generally match those for single bacterial strains, and vary among plant species. However, when the bacteria are exposed to a mixture of starches from different taxa, certain plants are digested in favor of others. This variation in digestion could lead to a bias in the starches represented in the archaeological record. The types of damage observed in this experiment are further compared against that observed on archaeological starches recovered from dental calculus and stone tools. Highlights: New experimental studies on bacterial digestion of single and mixed starches are presented. Starches from individual taxa in mixed samples degrade at different rates than when in isolation. Archaeological starches also show pitting from bacterial enzymes, which may actually indicate good preservation.